The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/fst.126421
|View full text |Cite
|
Sign up to set email alerts
|

Quinoa starch microspheres for drug delivery: preparation and their characteristics

Abstract: Quinoa starch microparticles (QSMs) fabricated with unhydrolyzed quinoa starch (QS) by inverse microemulsion technology could be used as medicine delivery and cosmetic accessories. The size distribution of QSMs was uniform at 28.5 μM, and the adsorption capacity of methylene blue was 0.82 mg/ g. The optimum preparation process was as follows: a QS mass fraction of 9%, an epoxy chloropropane content of 1%, an amount of oil phase of 100 mL, a span 80 of 3 mg/mL, and a stirring speed of 400 r/min for 3 h at room … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…The diameter values of the granules for each formulation are represented in Figure 8. As it is a fibrous material, we can observe that there are no spherical granules but rather irregular ones, with a variable polydispersity index, which is possibly a characteristic of this type of material [38]. It is noted that the granules are heterogeneous and have a wide size range varying from 439.00 to 1000.00 μm in average size.…”
Section: Granulometric Distribution and Granule Strengthmentioning
confidence: 84%
“…The diameter values of the granules for each formulation are represented in Figure 8. As it is a fibrous material, we can observe that there are no spherical granules but rather irregular ones, with a variable polydispersity index, which is possibly a characteristic of this type of material [38]. It is noted that the granules are heterogeneous and have a wide size range varying from 439.00 to 1000.00 μm in average size.…”
Section: Granulometric Distribution and Granule Strengthmentioning
confidence: 84%
“…The granule diameter values were heterogeneous and had a wide range at 996.41, 439.77, 766.21, 785.51, 579.56, 966.91, 800.44, 446.30, and 1040.71 μm, respectively (Figure 7). As it is a fibrous material, we can observe that there were no spherical granules but rather irregular ones, indicating that the granules have a variable polydispersity index (various dimensions), which is possibly a characteristic of this type of material [44]. Even with the variation in shape, the granules were mostly resistant, as shown in Table 7, and most formulations had an adequate flow (Figure 6), preventing these physical properties from being a limiting factor to producing chewable tablets.…”
Section: Optical Microscopymentioning
confidence: 93%
“…The encapsulation efficiency of rutin-loaded Pickering emulsions stabilized by amphiphilic quinoa starch reached as high as 99.3%, and sustained release was achieved in the in vitro studies [126]. Previous studies have indicated that microspheres with high adsorption capacity could be fabricated from quinoa seed starch, and could act as a promising material for drug delivery [127].…”
Section: Delivering Hydrophobic Bioactive Agentsmentioning
confidence: 94%